La religiosité des sans papiers mexicains de Deer Canyon, États-Unis - Philippe Schaffhauser (Les Cahiers ALHIM)
To the North of the San Diego Metropolitan in a ravine once called the deer Canyon area live more than 20 years, some undocumented Mexican. Different kind of odd, jobs used starting with the maintenance of houses of the billionaires residing on the top of the ravine. These migrants overpower their misery and social exclusion by developing a form of religiosity, which has attracted the interest of a few American Catholics in the region. In fact, a chapel was built. However under the pressure of riverside residents and real-estate brokers, this chapel was demolished and undocumented evacuated several times. Based on a couple of documentaries of an investigative reporter, John Carlos Frey, this article poses to discuss modalities of this form of religiosity and its impact on the lives of these migrants on the understanding that the Centre of gravity is the question on the modalities of believing. To study the subject, the article will get hand of different authors such as William James, Robert Musil, Georg Simmel, George Herbert Mead and Ludwig Wittgenstein.